Upaya Meningkatkan Minat Belajar Peserta Didik Pada Muatan Bahasa Madura Menggunakan Model Kooperatif Tipe Jigsaw Pada Kelas IV SDIT Ulil Albab Kamal Bangkalan - Faris Fansuri Dwi Santoso; Agung Setyawan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
learning is an activity that aims to change a person. The result of these activities are called learning outcomes. This research is aimed at increasing student’ learning interest in Madurese language content using a jigsaw cooperative model in class IV SDIT Ulil Albab. The method used in this study is the application of a jigsaw cooperative model with data collection methods in the form of questionnaires, observation, and documentation. The result of this study is that there is an were happier when they could freely larn on their own with their friends. In addition, in each cycle that occurred starting from cycle 1, a score of 82% was obtained for students who had an interest in learning ≥25(high learning interest category). Then in cycle 2, student interest in learning has reached 100% obtaining an interest in learning ≥25(high learning interest category).